A scoping review of behavior change techniques used to promote physical activity among women in midlife - Arigo, Danielle; Romano, Kelly A.; Pasko, Kristen; Travers, Laura; Ainsworth, M. Cole; Jackson, Daija A.; Brown, Megan M. (Frontiers in Psychology, 2022)
Women in midlife experience health risks that could be mitigated by regular physical activity (PA) and reduced sedentary time, but this population rarely achieves PA levels that would protect their health. As a result, many behavioral interventions are designed to promote PA in this population, which are purportedly guided by theoretical models of health behavior (change) and activate an associated set of behavior change techniques (BCTs). The efficacy and effectiveness of these interventions appear to be limited, however, raising questions about their design and adaptation for women in midlife. Several aspects of these interventions are currently unclear. Specifically, which women they target (i.e., how “midlife” and “sedentary” or “inactive” are defined), which theoretical models or behavior BCTs are used, and how BCTs are activated in such interventions. A synthesis of this information would be useful as an initial step toward improving PA interventions for this at-risk group, and thus, represented the goal of the present scoping review. Eligibility required publication in a peer-reviewed journal in English between 2000 and 2021, inclusion of only women in midlife who did not have any medical or other restrictions on their PA (e.g., cancer diagnosis), and free-living PA or sedentary behavior as the target outcome (with associated assessment). Of the 4,410 initial results, 51 articles met inclusion criteria, and these described 36 unique interventions. More than half of the articles (59%) named an underlying theoretical model and interventions included an average of 3.76 identifiable BCTs (range 1-11). However, descriptions of many interventions were limited and did not provide enough detail to determine whether or how specific BCTs were activated. Interventions also used a wide range of inclusion criteria for age range and starting activity level, which has implications for targeting/tailoring and effectiveness, and many interventions focused on marginalized populations (e.g., women from racial/ethnic minority backgrounds, those un- or under-insured). The present review identifies some strengths and highlights important limitations of existing literature, as well as key opportunities for advancing the design and potential utility of PA interventions for women in midlife.